TYPES OF LEXEMAS AND THEIR USAGE IN SPEECH (British Journal of Global Ecology and Sustainable Development, 2023)
Lexical unit of language is lexeme. A lexeme is a part of a word without suffixes that has a grammatical meaning, a unit specific to the vocabulary of a language. The meaning of a lexeme, the content that arises in a person's mind by connecting a set of certain sounds to a certain objective reality, that is, an object, an event, a sign, a characteristic, understood from it is called a lexical meaning.